Pharmacokinetics and Metabolism of Ziritaxestat (GLPG1690) in Healthy Male Volunteers Following Intravenous and Oral Administration. Issue 2 (11th October 2021) - Helmer, Eric; Willson, Ashley; Brearley, Christopher; Westerhof, Mark; Delage, Stephane; Shaw, Iain; Cooke, Ray; Sidhu, Sharan
Abstract: Ziritaxestat is a novel inhibitor of autotaxin, an enzyme responsible for the production of lysophosphatidic acid, the downstream signaling of which mediates responses to tissue injury and has been implicated in the pathogenesis of fibrotic conditions such as idiopathic pulmonary fibrosis and systemic sclerosis. This study (Clinical Trial Registration: NCT03787186) was designed to assess the absorption, distribution, metabolism, and excretion of orally administered 600‐mg ziritaxestat labeled with a carbon‐14 tracer ( 14 C‐ziritaxestat). To understand the absolute bioavailability of ziritaxestat, an intravenous 100‐μg microdose, labeled with a microtracer amount of 14 C radiation, was administered in a separate part of the study, following an unlabeled 600‐mg therapeutic oral dose of ziritaxestat. Six healthy male subjects completed each study part. The majority of the labeled oral dose was recovered in feces (77%), with a total mass balance of 84%. The absolute bioavailability of ziritaxestat was 54%. Ziritaxestat was the main (76%) circulating drug‐related product. There were 7 treatment‐emergent adverse events, all of which were considered mild and not considered to be related to the study drug.